DRAMATURGICALCONCEPTION FOR THEPROCCESSOFTEACHING - Chotimah, Ima Chusnul (JEELL (Journal of English Education, Linguistics and Literature), 2014)
This study  was conducted based on  the  level of the needs  toward  class‟smastery forteachers.Classmasterybecomesimportantfortheidealteaching-learning process.Theteacherswouldseemunprofessionalwhentheyarenotabletomasterthe class.From thisphenomenon,theresearchermadeaformulationby integratingseveral conceptsofclassmastery,bothpsychologically anddramaturgicallybecomeoneterm called "Dramaturgy ofTeaching".Forformulating,theresearcherusedBorg &Gall‟sResearch& Development.Theresultof  “DramaturgyofTeaching”formulationconsistsofsixsteps,namely;a)square  mapping   1  (understanding  student  expression  through  eyes  using  micro expressions),attractingstudents (engaging students'attentionwhiledetermining thechoice ofclassbackground),b)materialexplaining (explaining thematerialwhileintegrating gesture, blocking,gradation,intonation,and rhythm),3)squaremapping2(understanding studentexpressionon the responseofthe teacher'sexplanation),strengthening(giving reinforcementofmaterialwhile doing thesamethingwithb)),c)closing (closingwhile attractingattention, reinforcementmembers, andconveyingsomemessages).